PERAN NOTARIS SEBAGAI SAKSI DALAM PROSES PERADILAN PIDANA - Irawan Arief Firmansyah; Sri Endah Wahyuningsih (Jurnal Akta, 2017)
Research on "Notary's Role for Witnesses in Criminal Justice Process" to re-examine the authority of the Constitutional Court against notary notarization, the role of notary as the cost of criminal cases.MPD Regulation concerning notarial notes having domicile must be through MPD in accordance with Art. 66 (1) of Notary Act No. 30 Year. 2004 because it is not in line with the rules of Ps. 27 (1) and Psl. 28 D (1) of the 1945 Constitution on the equality of citizens' attitudes before the law in order to facilitate criminal justice for the realization of community justice. The role of a notary as a means in a criminal case is to provide information in accordance with the aspect of formal / material aspects of the deed which is the responsibility. Protection of a notary as a criminal offense after the release of the Constitutional Court verdict. 49 / PUU-X / 2012 is notary calling through Notary Board of Honor according to the provisions of Art. 66 Psl. UU no. 2 Yrs. 2014. In addition, the notary still gets an order from the rights and responsibilities of the notary public. Keywords: Notary, Witness, Criminal Case